2004
DOI: 10.1016/j.mser.2004.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Scaling, dimensional analysis, and indentation measurements

Abstract: We provide an overview of the basic concepts of scaling and dimensional analysis, followed by a review of some of the recent work on applying these concepts to modeling instrumented indentation measurements. Specifically, we examine conical and pyramidal indentation in elastic-plastic solids with power-law workhardening, in power-law creep solids, and in linear viscoelastic materials. We show that the scaling approach to indentation modeling provides new insights into several basic questions in instrumented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
537
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 943 publications
(573 citation statements)
references
References 252 publications
(305 reference statements)
25
537
0
11
Order By: Relevance
“…According to the manufacturer's instructions, both sides of samples were light cured for 20 seconds until the polymerization was carried out. Dimensional analysis applied to the samples used in the nano-indentation experiment showed that for a homogeneous material, the indentation test results were independent of all dimensions except depth [28], [29].…”
Section: Methodsmentioning
confidence: 99%
“…According to the manufacturer's instructions, both sides of samples were light cured for 20 seconds until the polymerization was carried out. Dimensional analysis applied to the samples used in the nano-indentation experiment showed that for a homogeneous material, the indentation test results were independent of all dimensions except depth [28], [29].…”
Section: Methodsmentioning
confidence: 99%
“…At low relative indentation depth the substrate contribution is minimal and the observed differences in x are due to differences in coating properties. FE analysis has predicted x ~5 [17][18] whilst for bulk materials experimental evidence suggests that x ~ 5 for glasses and x ~6-7 for metals [19][20]. For hard coating systems x has been reported to be ~6.4 on TiN-based nanocomposites [21] and 5.7 on TiAlCrN/TiAlCrSiYN multilayers [22].…”
Section: Nanoindentation and Plasticitymentioning
confidence: 99%
“…Chromik). the indentation size effect as a means to characterize the mechanical properties of materials [8,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%